Komunikasi Organisasi Pendidikan Di MIS Madinatussalam - Tasha aina; Luthfi Adam Lubis; Andini Zahara Simanjuntak; Mursal Aziz (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This article aims to determine the importance of educational organizational communication by using a descriptive qualitative research method, a literature approach and literature related to the theme of this research. The results of the author's analysis show that organizational communication is very necessary in running the organization of educational institutions, so there is good educational organizational communication at the MIS Madinatussalam school. The success of educational institutions is largely determined by management and organizational factors as well as the interpersonal communication skills possessed by each stakeholder in carrying out their duties. Effective communication can be seen from the best service and school management, the quality and excellence of graduates as expected by stakeholders, so communication skills for school personnel are indeed the task of school managers and leaders to always improve so that the benefits or contribution of communication skills and effectiveness in realizing achievements are clearer. educational goals in educational institutions.